2016
DOI: 10.1186/s13690-016-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between distorted body image and changes in weight status among normal weight preadolescents in Japan: a population-based cohort study

Abstract: BackgroundDistorted body image may be important risk factors for being underweight and overweight. The objective of this study was to investigate the association between having a distorted body image and being overweight or underweight among normal weight preadolescents in a population-based cohort study in Japan for each sex.MethodsThe study participants were 1431 normal weight fourth-grade students (age range: 9–10 years) in Ina town, Japan from 2002 to 2007. The height and weight of each student were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…This finding is consistent with the results of the studies [25,27]. Similarly, our results are compatible with the results of the studies [23,26] published previously. Our findings are also consistent with the study [24], which reported that weight-related anxiety is predictive for unhealthy eating attitudes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with the results of the studies [25,27]. Similarly, our results are compatible with the results of the studies [23,26] published previously. Our findings are also consistent with the study [24], which reported that weight-related anxiety is predictive for unhealthy eating attitudes.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the "distorted body image" concept was regarded as "perception of the self as heavy or thin while presenting with a normal weight." Results of the involving study suggested that a distorted body image during preadolescence is associated with being overweight or underweight in the following years [23]. It was reported that disordered eating was positively associated with the internalization of the thin ideal, weight-related anxiety and negatively associated with body image satisfaction.…”
Section: Perceived Weight and Body Imagementioning
confidence: 88%
“…Normal-weight children with overweight perception had increased risk of overweight/obesity. This finding is consistent with prior findings [ 12 , 13 , 28 ]. However, we should note that these children actually had less weight gain than their counterparts.…”
Section: Discussionsupporting
confidence: 94%
“…Personalized interventions in high-risk primary school children may effectively reduce the incidence of obesity during puberty and adulthood, and some cohort studies on adolescent obesity have also confirmed this view. 17 19 Preventive and proactive interventions would likely be highly cost-effective.…”
Section: Discussionmentioning
confidence: 99%